Hukum Pelaksanaan Tradisi Makan Hadap-Hadapan Adat Melayu: Studi Kasus di Hamparan Perak - Ardiansyah; Milhan (AL-SULTHANIYAH, 2025)
This research analyzes the law of the implementation of eating rice hadap-hadapan Malay custom (case study in Hamparan Perak). This research involves local Malay traditional leaders and people who have made eating hadap-hadapan as a necessary consideration in order to find out if there are problems in the implementation of eating hadap-hadapan Malay customs in Hamparan Perak from the sultanate period to the present and looking for sources of Islamic law to determine the law of the implementation of eating hadap-hadapan. This research uses an empirical approach method, namely (case study in Hamparan Perak), this method aims to explore and find out the thoughts and experiences of individuals or groups as a form of effort in answering the legal problems studied in this study. In this study, it was found that there was a redundancy that occurred in throwing rice in eating face-to-face rice. In Islam, if there is an act that is redundant or wasteful, it should be abandoned, but because eating face-to-face is a custom that has been passed down from generation to generation, this custom cannot be eliminated because it will damage the customs and characteristics of the tribe. So according to the author, the law of eating hadap-hadapan may be carried out but must avoid redundancy.